2015
DOI: 10.11114/jets.v3i5.858
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies Used to Improve Students’ Comfort and Skill in Addressing the Occupational Therapy Process

Abstract: The purpose of this study was to investigate the effectiveness of an intentional blending of instructional strategies in an occupational therapy (OT) entry-level master's course. The OT Adult Practice course uses case-based instructional strategies, clinical skills labs, and standardized patient experiences in a dovetailed approach across three progressively complex clinical scenarios involving adult clients. The course is designed to support students in addressing the entire OT Process. Results of quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Research testing the effect of using SPs with occupational therapy students is limited, but growing (Bennett et al, 2017). For example, a study by Knecht-Sabres et al (2013) using mixed methods with 74 students, evaluated the use of SPs in an adult intervention-focused course. The study found improved student self-perception of their level of comfort and skill with a set of competencies such as transfers, treatment plan development and clinical reasoning.…”
Section: Literature Review -The Value Of Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Research testing the effect of using SPs with occupational therapy students is limited, but growing (Bennett et al, 2017). For example, a study by Knecht-Sabres et al (2013) using mixed methods with 74 students, evaluated the use of SPs in an adult intervention-focused course. The study found improved student self-perception of their level of comfort and skill with a set of competencies such as transfers, treatment plan development and clinical reasoning.…”
Section: Literature Review -The Value Of Simulationmentioning
confidence: 99%
“…Many studies have noted the effectiveness of simulation on the development of student knowledge, confidence and reduction of anxiety, primarily within medical and nursing education (Alfes, 2011; Thomas and Mackay, 2012) but increasingly within allied health (Hill et al., 2013; Knecht-Sabres et al., 2013). In Alfes’ (2011) study of 63 nursing students learning to care for patients experiencing pain, results indicated that students in the simulation group reported feeling more confident than those who received a traditional demonstrative approach.…”
Section: Literature Review – the Value Of Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational therapy educators use a variety of simulation forms, including standardized patients (SPs), for foundational courses, as preparation for fieldwork, and to address competencies (Bennett et al, 2017). The use of a combination of client cases, labs, and SPs can improve students' perception of comfort and skill level in key competency areas (Knecht-Sabres et al, 2013;Knecht-Sabres et al, 2015). Occupational therapy students have reported learning more from live simulated cases than lecture and role play methods (Velde et al, 2009), perceived interventions with SPs as valuable (Walls et al, 2019), and reported SPEs to be useful or very useful (Herge et al, 2013).…”
Section: Introductionmentioning
confidence: 99%